بیٹیوں کی وراثت کے معاشرتی مسائل اور ان کا حل قرآن و سنت کی روشنی میں - Ahmad Raza; Syed Waheed Ahmad (Pakistan Journal of Islamic Research)
In Islam bringing up girls is strongly appreciated. Prophet Muhammad (SAW) promised the one who brings up their girls properly that he would accompany him in paradise. To understand why the noble Prophet Muhammad, peace and blessings be upon him, empathized the well bringing up of girls we have to know that in the Arabic society before Islam, fathers used to feel disgraced when a daughter is born to him. They used to bury the girl alive to get rid of the shame. They considered the daughter as inferior to the son. In fact, only few of them were a bit fair to girls. Fighting such an unfair attitude was one of the main issues in Islam that came with the major concept of equality between all races, “An Arab is not better than a non-Arab and a non-Arab is not better than an Arab”. To fulfill this concept Islam had to fight sex discrimination. Islam fought this discrimination in various ways in which Islam ensured the rights of women whether as a mother, wife or daughter. This article deals with the social issues of daughter’s inheritance. We highlighted these problems and suggested the resolutions in this article.